1990
DOI: 10.1017/s0899367x00002166
|View full text |Cite
|
Sign up to set email alerts
|

Investment Behavior and Energy Conservation

Abstract: Binary logit and bivariate probit models were used to investigate the investment behavior of farmers relative to two energy-conserving assets, heat-recovery systems and precoolers. The bivariate probit procedure was useful in correcting for self-selectivity bias. Holdout samples and cross-validation procedures were used to develop true model statistics. Farm size, educational level of the operator, and the type of milking system in use were the important factors influencing investment behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This understanding of the groups helps the decision of farmers to subscribe to such groups. In other studies, educational attainment was also found to influence farmers' willingness to apply best management practices (Chang and Boisvert 2005;Drost, Long and Hale 1998;Ladue, Miller and Kwiatkowski 1990;Obubuafo, Gillespie, Paudel and Kim, 2008;Paudel and Devkota, 2007). This implies that education is an important variable in the farmers' decision making process.…”
Section: Estimation Of Farmers' Willingness To Subscribe To Farmers' mentioning
confidence: 85%
See 2 more Smart Citations
“…This understanding of the groups helps the decision of farmers to subscribe to such groups. In other studies, educational attainment was also found to influence farmers' willingness to apply best management practices (Chang and Boisvert 2005;Drost, Long and Hale 1998;Ladue, Miller and Kwiatkowski 1990;Obubuafo, Gillespie, Paudel and Kim, 2008;Paudel and Devkota, 2007). This implies that education is an important variable in the farmers' decision making process.…”
Section: Estimation Of Farmers' Willingness To Subscribe To Farmers' mentioning
confidence: 85%
“…Jensen et al (2012) observed positive significant relationship between poultry farmers' willingness to participate in energy audit and their socio-economic characteristics. Previous studies show that farm size positively affects farmers' willingness to adopt, for example, environmentally beneficial practices (Chang and Boisvert 2005;Fernandez-Cornejo, Beach and Huang 1994;Hua, Zulauf and Sohngen 2004;Ladue, Miller and Kwiatkowski 1990;Upadhyay, Young, Wang and Wandschneider 2002). Willingness to adopt best management practices on poultry operations is positively influenced by farm income (Paudel and Devkota 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation